Marital satisfaction, gender equity, and marital conflict among selected elderly couples in Guimbal, Iloilo - Asorio, Shiela Mae Sitcharon; Pradilla, Lea Angela
The study was conducted to find out the relationship among marital satisfaction, gender equity, and marital conflict among old married couples, as well as their pattern of conflict resolution. Nineteen (19) elderly couples from Guimbal married for at lest 25 years and living with their families at the time of the study participated., The instrument used were the shortened version of the Comprehensive Marital Satisfaction Scale by Blum and Mehrabian (1999), the Gender Equity on Household Labor Scale, and the Conflict Resolution Questionnaire. Results show that marital satisfaction and marital conflict have a significant negative correlation at -0.460 [a=0.01 level of significance (2-tailed test)]. The mean score marital conflict at 0.252 [a=0.01 level of significance (2 tailed test)]. The mean score (19.29) on the shortened version of the Comprehensive Marital Satisfaction Scale by Blum and Mehrabian (1999) indicates that the respondents have high level of marital satisfaction. There was also significant gender difference in the distribution of household labor perceived by the males and females with to=-16.36 (tc+<-2.042 or 2.042). Lastly, with regards conflict resolution, majority of the respondents use the compromise style. The outcomes of the study support previous studies which state that elderly marriages experience high level of marital satisfaction and less marital conflict.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Marriage -- Guimbal, Iloilo